Influence of Work Stress, Work Environment and Work Discipline on Employees Performance At PT. Artindo Artamas - Aderia Kusuma; Diana Silaswara (Fakultas Bisnis, 2023)
The motivation behind this examination is to figure out the issues related to employee performance, especially those related to the influence of work stress, work environment, and work discipline at PT. Artindo Artamas. The data survey and collection was distributed to 100 respondents with clear objectives and was completed through an overview spread. Data analysis was carried out using the SPSS version 25 program. This study used descriptive test data testing techniques, validity tests, reliability tests with alpha-cronbach. Test simple linear regression analysis to test and prove hypotheses in research. The worth of the coefficient of determination shows the number 0.370. This implies that the influence of work stress, work environment and work discipline on employee performance is 37% while the rest (100% -37% = 63%). The Fcount value is 18.669 with a significance of 0.000 less than 0.05 and also Fcount > Ftable or 18.669 > 2.70. The beta coefficient of work stress -0.154, work environment 0.080, and work discipline have a strong positive and massive impact of 0.581. This means that there is a substantial connection between work stress, work environment and work discipline on the quality of employee performance